Take away the A : an alphabeast of a book! - d uthor; DiGiacomo, Kris (New York : Enchanted Lion Books, 2014)
What happens when you subtract just one letter from a word? Beginning with "without the A the beast is the best" a pack of silly creatures work their way through the alphabet, subtracting each letter from a different word to alter its meaning and tell a story.
"An alphabeast of a book!"
Keywords: Alphabet; Grammar, Comparative and general -- Word formation; Animals -- Juvenile fiction; Plays on words -- Juvenile fiction; Alphabet; Animals -- Fiction; Plays on words -- Fiction